Some Results on Pell’s Equation: Exploring Special Characters and Diophantine Solutions of Pell’s Equation (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper we shall define and discuss about some special characters of Pell’s equation and a very simple verified results on Pell’s equation to show that, one can find more solution of Pell’s equation which give rise to next some another solution by continued fraction in a very simple manner. With the help of convergence of continued fraction expansion of in the Pell’s equation , we shall find out Diophantine pair solution of Pell’s equation under certain condition. At last we shall get some recent results on Pell’s equation.